Novel approach to enhance film properties of environmentally friendly UV-curable alkyd coating using epoxidised natural rubber - Desmond, T.C.A.; Yoke, K.K.; Seng, N.G. (Elsevier, 2013)
Environmental friendly coatings have gained popularity and importance owing to the implementation of various environmental legislations to curb the emission of air pollutants. The present work deals with the conversion of non-self drying palm stearin alkyd into UV curable coating, followed by enhancement of the film properties of the coating using epoxidised natural rubber (ENR). Alkyd was synthesised using palm stearin as the source of fatty acids and it was rendered UV-curable by increasing the level of unsaturation through incorporation of fumaric acid. The alkyd was characterised via 1H NMR and FTIR before it was formulated into coating mixture, with methyl methacrylate (MMA) as reactive diluent and benzophenone as UV photoinitiator. Another two sets of coating mixtures, AlkE25 and AlkE50, were prepared using fumarised alkyd incorporated with ENR25 and ENR50, respectively. The incorporation was achieved through the reaction involving epoxide group of ENR and COOH group of alkyd. AlkE25 and AlkE50 coatings have better film properties than the control coating (formulated without ENR) attributed to the increase in the crosslink density that results from the introduction of ENR into the coating formulation.